Opportunity Cost from The Perspective of Lontarak Kotika: A Review of Bugis Makassar Local Wisdom - Aswad Syam; Muh. Akob Kadir; Lusiana Kanji (Golden Ratio of Auditing Research, 2026)
This research aims to examine the concept of opportunity cost from the perspective of Bugis-Makassar local wisdom through the manuscript Lontarak Kotika. As a traditional text containing cosmological knowledge of auspicious and inauspicious days, Lontarak Kotika has long guided the Bugis-Makassar people in making crucial decisions, such as farming, sailing, trading, and performing customary rituals. Using a qualitative approach with an interpretive paradigm and ethnomethodology, this study explores the meanings and practices of opportunity cost manifested in local traditions. The research informants consist of community elders, farmers, fishermen, traders, and cultural experts in Bone and Takalar. Data were collected through in-depth interviews, participant observation, and document studies of Lontarak Kotika. The findings reveal that the Bugis-Makassar community interprets opportunity cost not only within the framework of formal economics but also within cosmological and spiritual horizons. For instance, postponing rice planting on days deemed inauspicious is considered a short-term sacrifice to avoid greater losses, both material and social. In this sense, opportunity cost encompasses not only forgone harvests and time but also cultural legitimacy. This study contributes to academic discourse by enriching interdisciplinary literature, particularly the intersection between economics and cultural anthropology. Practically, it offers a model of understanding opportunity cost grounded in local wisdom as a reference in economic decision-making. Culturally, it reaffirms the relevance of Lontarak Kotika as a traditional compass that remains adaptive in navigating modernity.